Polygonal Dipole Placements for Efficient, Rotatable, Single Beam Smart Antennas in 5G Aerospace and Ground Wireless Systems - Pirapaharan, K.; Hoole, P.R.P; Norhuzaimin, Julai; Al-Khalid, Othman; Ade Syaheda Wani, Marzuki; Senthilkumar, K.S.; Hoole, S.R.H. (Universiti Teknikal Malaysia (UTEM), 2017)
In telecommunication systems and radars, the common practice in using array antennas is to place a reflector behind the array so as to reflect the backward signal also in the forward direction. Moreover, in the 5G wireless systems, smart antennas, especially those with a single beam, are expected to play a critical role in its successful launching in 2020. We show in this paper that a linear array antenna necessarily ends up with symmetrical beamforming on both sides of the array axis. Thus, single direction (forward direction) beamforming cannot be achieved by placing the electromagnetic radiators (e.g. dipole elements) in a straight line. We propose that in situations where a smart array structure demands single rotatable beams, that single rotatable beamforming can be achieved by changing the geometrical shape of the array. However, the computational intensity involved in finding optimized weight coefficients for beamforming over the entire 360o space turns into the major challenge. In order to minimize the computational repetition of optimizing weights for every direction, a regular polygon array antenna is proposed. We show that an array antenna placed in a regular polygon yields a smart antenna with a highly effective and computationally fast, reduced memory and electronically rotatable single beam.